Spatial patterns of soil pathogens in declining Mediterranean forests: implications for tree species regeneration. - Gómez-Aparicio, LORENA; Ibáñez, Beatriz; Serrano, María S.; De Vita, Paolo; Avila, José M.; Pérez-Ramos, Ignacio M.; García, Luis V.; Esperanza Sánchez, M.; Marañón, Teodoro (The New phytologist, 2012)
Soil-borne pathogens are a key component of the belowground community because of the significance of their ecological and socio-economic impacts. However, very little is known about the complexity of their distribution patterns in natural systems. Here, we explored the patterns, causes and ecological consequences of spatial variability in pathogen abundance in Mediterranean forests affected by oak decline. We used spatially explicit neighborhood models to predict the abundance of soil-borne pathogen species (Phytophthora cinnamomi, Pythium spiculum and Pythium spp.) as a function of local abiotic conditions (soil texture) and the characteristics of the tree and shrub neighborhoods (species composition, size and health status). The implications of pathogen abundance for tree seedling performance were explored by conducting a sowing experiment in the same locations in which pathogen abundance was quantified. Pathogen abundance in the forest soil was not randomly distributed, but exhibited spatially predictable patterns influenced by both abiotic and, particularly, biotic factors (tree and shrub species). Pathogen abundance reduced seedling emergence and survival, but not in all sites or tree species. Our findings suggest that heterogeneous spatial patterns of pathogen abundance at fine spatial scale can be important for the dynamics and restoration of declining Mediterranean forests.
The following values have no corresponding Zotero field: accession-num: 22428751
Keywords: Biological; Forest decline; Host-Pathogen Interactions; Mediterranean Region; Models; neighborhood models; Phytophthora; Phytophthora: physiology; Pythium; Pythium: physiology; Quercus; Quercus suber; Quercus: microbiology; regeneration dynamics; Seedling; Seedling: microbiology; Soil Microbiology; soil texture; soil-borne pathogens; species coexistence

Use of an airborne lidar system to model plant species composition and diversity of Mediterranean oak forests. - Simonson, William D; Allen, Harriet D; Coomes, David A (Conservation biology : the journal of the Society for Conservation Biology, 2012)
Airborne lidar is a remote-sensing tool of increasing importance in ecological and conservation research due to its ability to characterize three-dimensional vegetation structure. If different aspects of plant species diversity and composition can be related to vegetation structure, landscape-level assessments of plant communities may be possible. We examined this possibility for Mediterranean oak forests in southern Portugal, which are rich in biological diversity but also threatened. We compared data from a discrete, first-and-last return lidar data set collected for 31 plots of cork oak (Quercus suber) and Algerian oak (Quercus canariensis) forest with field data to test whether lidar can be used to predict the vertical structure of vegetation, diversity of plant species, and community type. Lidar- and field-measured structural data were significantly correlated (up to r= 0.85). Diversity of forest species was significantly associated with lidar-measured vegetation height (R(2) = 0.50, p < 0.001). Clustering and ordination of the species data pointed to the presence of 2 main forest classes that could be discriminated with an accuracy of 89% on the basis of lidar data. Lidar can be applied widely for mapping of habitat and assessments of habitat condition (e.g., in support of the European Species and Habitats Directive [92/43/EEC]). However, particular attention needs to be paid to issues of survey design: density of lidar points and geospatial accuracy of ground-truthing and its timing relative to acquisition of lidar data.
Keywords: Biodiversity; Biological; cluster analysis; Conservation of Natural Resources; Conservation of Natural Resources: methods; Ecosystem; mediterranean oak forest; Models; Portugal; predictive modeling; Quercus; Remote sensing; Remote Sensing Technology; Remote Sensing Technology: methods; Species Specificity; vascular plants

Social amoebae: environmental factors influencing their distribution and diversity across south-western Europe. - Romeralo, María; Moya-Laraño, Jordi; Lado, Carlos (Microbial ecology, 2011)
The social amoebae (dictyostelids) are the only truly multicellular lineage within the superkingdom Amoebozoa, the sister group to Ophistokonts (Metazoa+Fungi). Despite the exceptional phylogenetic and evolutionary value of this taxon, the environmental factors that determine their distribution and diversity are largely unknown. We have applied statistical modeling to a set of data obtained from an extensive and detailed survey in the south-western of Europe (The Iberian Peninsula including Spain and Portugal) in order to estimate some of the main environmental factors influencing the distribution and diversity of dictyostelid in temperate climates. It is the first time that this methodology is applied to the study of this unique group of soil microorganisms. Our results show that a combination of climatic (temperature, water availability), physical (pH) and vegetation (species richness) factors favor dictyostelid species richness. In the Iberian Peninsula, dictyostelid diversity is highest in colder and wet environments, indicating that this group has likely diversified in relatively cold places with high levels of water availability.
Keywords: Biodiversity; Biological; Dictyosteliida; Dictyosteliida: classification; Dictyosteliida: genetics; Dictyosteliida: isolation & purification; Dictyosteliida: physiology; Ecosystem; Models; Portugal; Soil; Soil: parasitology; SPAIN (citation)

Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. - Grote, Rüdiger; LAVOIR, ANNE-VIOLETTE; Rambal, Serge; Staudt, Michael; Zimmer, Ina; Schnitzler, Jörg-Peter (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.
Keywords: Biological; Carbon dioxide; Carbon Dioxide: metabolism; Computer Simulation; Drought impact; Droughts; France; Model coupling; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: physiology; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: metabolism; Scaling; Trees; Trees: metabolism; water; Water: metabolism

Plasticity and stress tolerance override local adaptation in the responses of Mediterranean holm oak seedlings to drought and cold - Gimeno, Teresa E; Pías, Beatriz; Lemos-Filho, José P; Valladares, Fernando (Tree Physiology, 2009)
Plant populations of widely distributed species experience a broad range of environmental conditions that can be faced by phenotypic plasticity or ecotypic differentiation and local adaptation. The strategy chosen will determine a population’s ability to respond to climate change. To explore this, we grew Quercus ilex (L.) seedlings from acorns collected at six selected populations from climatically contrasting localities and evaluated their response to drought and late season cold events. Maximum photosynthetic rate (Amax), instantaneous water use efficiency (iWUE), and thermal tolerance to freeze and heat (estimated from chlorophyll fluorescence versus temperature curves) were measured in 5-month-old seedlings in control (no stress), drought (water-stressed), and cold (low suboptimal temperature) conditions. The observed responses were similar for the six populations: drought decreased Amax and increased iWUE, and cold reduced Amax and iWUE. All the seedlings maintained photosynthetic activity under adverse conditions (drought and cold), and rapidly increased their iWUE by closing stomata when exposed to drought. Heat and freeze tolerances were similarly high for seedlings from all the populations, and they were significantly increased by drought and cold, respectively; and were positively related to each other. Differences in seedling performance across populations were primarily induced by maternal effects mediated by seed size and to a lesser extent by idiosyncratic physiologic responses to drought and low temperatures. Tolerance to multiple stresses together with the capacity to physiologically acclimate to heat waves and cold snaps may allow Q. ilex to cope with the increasingly stressful conditions imposed by climate change. Lack of evidence of physiologic seedling adaptation to local climate may reflect opposing selection pressures to complex, multidimensional environmental conditions operating within the distribution range of this species.
10.1093/treephys/tpn007
Keywords: Adaptation; Biological; Biological: physiology; Cold Temperature; Droughts; eﬃciency; Freezing; Genetic Variation; Hot Temperature; Nuts; photosynthesis; Photosynthesis: physiology; Physiological; Quercus; Quercus ilex; Quercus: physiology; Stress; thermal tolerance; Trees; water; water use; Water: physiology

Sensitivity of volatile monoterpene emission to changes in canopy structure: a model-based exercise with a process-based emission model - Grote, Rüdiger (New Phytologist, 2007)
* • This paper investigates the dependence of monoterpene emissions at the canopy scale on total leaf area and leaf distribution. Simulations were carried out for a range of hypothetical but realistic forest canopies of the evergreen Quercus ilex (holm oak). * • Two emission models were applied that either did (SIM-BIM2) or did not (G93) account for cumulative responses to temperature and light. Both were embedded into a canopy model that considered spatial and temporal variations of foliage properties. This canopy model was coupled to a canopy climate model (CANOAK) to determine the micrometeorological conditions at the leaf scale. * • Structural properties considerably impacted monoterpene emission. The sensitivities to changes in total leaf area and to leaf area distribution were found to be of similar magnitude. The two different models performed similarly on a whole-year basis but showed clear differences during certain episodes. * • The analysis showed that structural indices have to be carefully evaluated for proper scaling of emission from leaves to canopy. Further research is encouraged on seasonal dynamics of emission potentials.
Keywords: Biological; biomass; foliage distribution; leaf area index; light; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: radiation effects; Plant Leaves; Plant Leaves: metabolism; Plant Leaves: radiation effects; Quercus; Quercus ilex; Quercus: metabolism; Quercus: radiation effects; Scaling; stand density; Temperature; Time Factors; Volatilization

Prediction of near-surface soil moisture at large scale by digital terrain modeling and neural networks. - Lavado Contador, J F; Maneta, M; Schnabel, S (Environmental monitoring and assessment, 2006)
The capability of Artificial Neural Network models to forecast near-surface soil moisture at fine spatial scale resolution has been tested for a 99.5 ha watershed located in SW Spain using several easy to achieve digital models of topographic and land cover variables as inputs and a series of soil moisture measurements as training data set. The study methods were designed in order to determining the potentials of the neural network model as a tool to gain insight into soil moisture distribution factors and also in order to optimize the data sampling scheme finding the optimum size of the training data set. Results suggest the efficiency of the methods in forecasting soil moisture, as a tool to assess the optimum number of field samples, and the importance of the variables selected in explaining the final map obtained.
Keywords: Biological; Dehesa; forecasting soil moisture; humidity; Models; Neural Networks (Computer); sampling; Soil; topographic variables